Determinants of Sorghum Farmers' Decisions to Adopt New Superior Varieties: Evidence from Lamongan Regency - Zuhriyah, Tsaniyatus; Priyanto, Moh. Wahyudi (Program Studi Agribisnis INSTIPER Yogyakarta, 2024)
Sorghum as an alternative commodity to substitute rice and other cereal crops, showing to its high adaptability to arid environments and limited rainfall. However, sorghum production has witnessed a decline, leading to a reduction in sorghum supply, thus impacting the provision of food and raw materials for industries. This research aims to ascertain farmers' decisions in selecting new superior varieties (NSV) and whether the utilization of NSV enhances farmers' productivity and income. The study was conducted in Patihan Village, Lamongan Regency, with a sample size of 55 sorghum farmers. Logistic regression analysis was employed to determine the factors influencing farmers in adopting new superior sorghum varieties. The findings indicate that factors influencing farmers in utilizing NSV include education, land size, farming experience, participation in farmer groups, and harvest orientation. Although the utilization of NSV does not increase sorghum farmers' productivity, the income of sorghum farmers adopting NSV has increased.